Pengaturan Pemberhentian Notaris Secara Tidak Hormat Akibat Dinyatakan Pailit - Gama, Kadek Liana Satwikha; Resen, Made Gde Subha Karma (Acta Comitas, 2023)
The writing of this research is primarily aimed at conducting an analysis of the arrangements and the legal consequences of dismissal, in this case a Notary who is declared bankrupt. This writing uses a normative legal research method by studying UUJN and UUK PKPU, using a statutory approach and conceptual analysis approach, in writing this research also uses a reference material, namely primary legal material as the main reference material in the form of related literature, secondary legal materials such as journals, as well as tertiary legal materials to support this research can certainly provide an in-depth understanding of the matter being analyzed, the results of the study and analysis of this research are explained qualitatively with descriptive explanations. The results of the research are arrangements for dismissing a Notary due to bankruptcy regulated in UUJN which stipulates that a Notary who is declared bankrupt is a Notary with a legal subject who has two or more creditors and is unable to fulfill his obligations to pay off debts. This can also be caused because in committing a loss to the the parties and the Notary are unable to be held responsible for the actions committed so that the Notary is declared bankrupt by the Commercial Court and is considered unable to carry out a legal action because he is under guardianship. This is what causes a Notary to be considered incompetent. As a result of the law, the Notary was dismissed dishonorably because he was declared bankrupt, so the Notary was deemed incompetent and lost his position authority in accordance with UUJN and his position had to be replaced by a Substitute Notary to submit a notary protocol whose position is a state-owned confidential document.   Keywords: Notary, Disrespectful Dismissal, Bankruptcy